2015
DOI: 10.1128/mcb.01432-14
|View full text |Cite|
|
Sign up to set email alerts
|

Nuclear GIT2 Is an ATM Substrate and Promotes DNA Repair

Abstract: Insults to nuclear DNA induce multiple response pathways to mitigate the deleterious effects of damage and mediate effective DNA repair. G-protein-coupled receptor kinase-interacting protein 2 (GIT2) regulates receptor internalization, focal adhesion dynamics, cell migration, and responses to oxidative stress. Here we demonstrate that GIT2 coordinates the levels of proteins in the DNA damage response (DDR). Cellular sensitivity to irradiation-induced DNA damage was highly associated with GIT2 expression levels… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
68
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 27 publications
(72 citation statements)
references
References 54 publications
4
68
0
Order By: Relevance
“…Using a combinatorial informatics and proteomics approach, we demonstrated that GIT2 acts as a hypothalamic aging “keystone” factor ( 13 ). Subsequently, GIT2 has also been implicated in regulating DNA integrity via its interaction with ataxia telangiectasia-mutated (ATM), a DNA damage repair (DDR) kinase ( 18 ). In response to multiple forms of DNA damaging insults, GIT2 is rapidly phosphorylated by ATM and then forms a complex with multiple DDR proteins including MDC1, MRE11, and phosphorylated H2AX ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using a combinatorial informatics and proteomics approach, we demonstrated that GIT2 acts as a hypothalamic aging “keystone” factor ( 13 ). Subsequently, GIT2 has also been implicated in regulating DNA integrity via its interaction with ataxia telangiectasia-mutated (ATM), a DNA damage repair (DDR) kinase ( 18 ). In response to multiple forms of DNA damaging insults, GIT2 is rapidly phosphorylated by ATM and then forms a complex with multiple DDR proteins including MDC1, MRE11, and phosphorylated H2AX ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, GIT2 has also been implicated in regulating DNA integrity via its interaction with ataxia telangiectasia-mutated (ATM), a DNA damage repair (DDR) kinase ( 18 ). In response to multiple forms of DNA damaging insults, GIT2 is rapidly phosphorylated by ATM and then forms a complex with multiple DDR proteins including MDC1, MRE11, and phosphorylated H2AX ( 18 ). Genomic deletion of GIT2 in mice (GIT2KO) resulted in a significant increase in the rate of DNA damage accumulation compared to wild type (WT) age-matched control mice ( 18 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…of damage (Frank and Hansen, 2008;Lu et al, 2015). GIT-PIX complexes are dynamic within cells and exhibit high mobility among compartments, such as when cells adhere or migrate (Manabe et al, 2002) or during activation of chromaffin cells to release stored vesicles (Meyer et al, 2006).…”
Section: Git Proteinsmentioning
confidence: 99%
“…Our proteomic analysis pipelines and methodologies have previously been demonstrated to be both rigorous and able to generate highly effective and significant data outputs that give actionable, high-dimensionality data appreciation [17][18][19][20][21][22][23][24].…”
Section: Statistical Analysesmentioning
confidence: 99%